2015
DOI: 10.3174/ajnr.a4629
|View full text |Cite
|
Sign up to set email alerts
|

Cough-Associated Changes in CSF Flow in Chiari I Malformation Evaluated by Real-Time MRI

Abstract: BACKGROUND AND PURPOSE:Invasive pressure studies have suggested that CSF flow across the foramen magnum may transiently decrease after coughing in patients with symptomatic Chiari I malformation. The purpose of this exploratory study was to demonstrate this phenomenon noninvasively by assessing CSF flow response to coughing in symptomatic patients with Chiari I malformation by using MR pencil beam imaging and to compare the response with that in healthy participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…22,[33][34][35] These studies also demonstrated that there was minimal if any pressure dissociation in these patients with CMI at rest before coughing or Valsalva. 33 While we did not calculate pressure gradients from our velocity data, our results confirmed both of these observations made by previous invasive pressure studies. 34,35,41 First, a decrease in CSF flow after coughing in patients with CMI indicates that CSF circulation from the head to spine is impaired, a condition that would result in pressure dissociation.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…22,[33][34][35] These studies also demonstrated that there was minimal if any pressure dissociation in these patients with CMI at rest before coughing or Valsalva. 33 While we did not calculate pressure gradients from our velocity data, our results confirmed both of these observations made by previous invasive pressure studies. 34,35,41 First, a decrease in CSF flow after coughing in patients with CMI indicates that CSF circulation from the head to spine is impaired, a condition that would result in pressure dissociation.…”
Section: Discussionmentioning
confidence: 55%
“…21,23,24,[32][33][34][35] The development of pressure dissociation is explained by a transient increase in spinal pressure (from increased intrathoracic pressure and consequent distension of the epidural veins) during coughing, moving CSF to the head, which returns to the spinal canal immediately postcoughing in a healthy subject but not in a patient with CMI, provided there is sufficient foramen magnum obstruction due to neural crowding. 22,[33][34][35] These studies also demonstrated that there was minimal if any pressure dissociation in these patients with CMI at rest before coughing or Valsalva. 33 While we did not calculate pressure gradients from our velocity data, our results confirmed both of these observations made by previous invasive pressure studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations